Smelling - Katz, Susan B., 1971- (New York : Children's Press, an imprint of Scholastic Inc., 2024)
"The Learn About series gives readers a close-up look at the five senses, and it teaches them how each of the senses work"--
"How do we experience the world? Let's learn all about the five senses!The sense of smell is one of our five senses. And it is amazing! It helps us recognize different smells, it brings back memories, and it keeps us safe. Smelling also enhances the taste of what we are eating! Learn about smelling, how it works, and common problems and diseases connected with it, with this perfect first introduction to the sense of smell!ABOUT THE SERIES:The human body is amazing! It gives us five different ways to learn about the world around us: through the eyes, through the skin, through the tongue, through the ears, and through the nose. Thanks to these parts of our bodies, we can see, feel, taste, hear, and smell. These are the five senses! Why do bananas taste so good? Why does tickling cause so much laughter? Illustrated with familiar examples, this fun nonfiction set in the Learn About series gives readers a close-up look at the five senses, and it teaches them how each of the senses work"--
Introduction: Take a deep breath! -- Right on the nose -- How our nose works -- Nose issues -- Smell stroll -- Animal smell -- Protect your nose.
Includes index.
Ages 5-7
Grades K-1
Keywords: Smell -- Juvenile literature; Nose -- Juvenile literature; Senses and sensation -- Juvenile literature; JUVENILE NONFICTION / Concepts / Senses & Sensation; JUVENILE NONFICTION / General